Zoo design – micro-landscapes and biodiversity, the master plan of sóstó zoo - Fekete, Orsolya (4D Journal of Landscape Architecture and Garden Art, 2015)
Designing a zoo primary means creating hygienic, safe, comfortable and diverse habitats for animals. At the same time zoo design focuses on an institutional garden, which functions as a walkable recreational spatial structure dedicated for the visitors by offering a harmonic, informative environment that provides livable experiences. Zoos are also sustainable nature conservation centers, led by scientific and ecological aims.
Keywords: zoo design; micro-landscapes and biodiversity